Analysis on Investment of Small and Medium Entrepreneurship - Kiseleva, Olga V.; Pinkovetskaia, Iuliia S. (International Journal of Economics and Financial Issues, 2016)
The article presents the results of the author's analysis and evaluation of investments in small and medium entrepreneurship, the empirical testing of hypotheses about the presence of the differentiation value of investment and the possibility of describing the existing regularities with the use of economic and mathematical models. During models` constructing we used official statistical indicators characterizing the set of small enterprises, medium enterprises and individual entrepreneurs in all regions of the Russian Federation. There are two classes of models describing the volumes of investments accounted, respectively, to one entrepreneurial structure and one employee. Logical and statistical analysis showed that all developed models are approximate well the original data over the entire range of their changes. It is proved that the volume of investment, both in terms of entrepreneurial structure and one of its employees differs significantly depending on the number of employees of entrepreneurial structures, regions, and economic activities, which specialize in entrepreneurial structures. The developed model and the resulting patterns can be used to solve a wide range of tasks while monitoring business activities, development design and forecasting in this sector of the economy at the federal, regional and municipal levels of management. Keywords: Small and medium enterprises; individual entrepreneurs; investment; economic and mathematical models; regions of the country. JEL Classifications: L26; O16